2017
DOI: 10.1108/lhs-12-2015-0055
|View full text |Cite
|
Sign up to set email alerts
|

Leading nurses: emotional intelligence and leadership development effectiveness

Abstract: Purpose The purpose of this paper is to examine the effectiveness of an emotional intelligence (EI) and leadership development education program involving 20 nurse leaders at nursing homes. Also, it investigates the relationship between EI and transformational leadership. Design/methodology/approach Three research questions are posed. Correlation analysis and t-tests were conducted to answer the questions posed. Findings The findings of this paper indicate that the EI educational development was effective, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 66 publications
3
29
0
1
Order By: Relevance
“…These results are consistent with other training interventions that have obtained positive results in their participants' EI development [60]. The satisfactory experiences of EI training for healthcare professionals have taken place in a wide range of contexts, ranging from intensive care [61] to long-term care in nursing homes [62], including clinical areas [63][64][65]. Indeed, EI training has not only increased these skills in healthcare professionals but has also been associated with the patients' quality of life [63], professionals' job performance and job retention [64], their perceived state of health [61] and patient satisfaction [64].…”
Section: Discussionsupporting
confidence: 84%
“…These results are consistent with other training interventions that have obtained positive results in their participants' EI development [60]. The satisfactory experiences of EI training for healthcare professionals have taken place in a wide range of contexts, ranging from intensive care [61] to long-term care in nursing homes [62], including clinical areas [63][64][65]. Indeed, EI training has not only increased these skills in healthcare professionals but has also been associated with the patients' quality of life [63], professionals' job performance and job retention [64], their perceived state of health [61] and patient satisfaction [64].…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, Zhang et al (2018) suggested that employees who perceive higher levels of empowerment are more likely to build robust credential motivation to achieve better engagement in their workplace. Nurse managers have a major influence on workplace cultures (Newman et al, 2015), so they need access to development programmes focusing on their EI and EL skills (Crowne et al, 2017). A strong leadership support and a training programme will improve emotional identification and emotion management abilities among staff nurses trained in EI and EL (Crowne et al, 2017;Davies et al, 2010).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…In their literature review Akerjordet and Severinsson (2008) reported emotional intelligence (EI) important in nurse leadership for contributing toward nurse empowerment and positive organisational outcomes. To analyse EI further, Crowne et al (2017) used quantitative methods to investigate if EI could be improved for NLs (N=20) following a three year education programme, and to explore the relationship between EI and transformational leadership, which encourages, inspires, and motivates employees toward positive practice outcomes (Bass & Riggio, 2006). The authors define EI as "an ability to focus on the accurate perception and expression of emotion; understand emotional knowledge; use feelings to facilitate thought; and regulate emotions in oneself and others" (p.219).…”
Section: Personal Traitsmentioning
confidence: 99%
“…Before and after evaluation techniques were employed using the Multifactor Leadership Questionnaire (MLQ) to measure transformational leadership qualities (idealized influence, inspirational motivation, intellectual stimulation and individual consideration) (Avolio & Bass, 2004) and EQ-I to measure EI qualities (intrapersonal, interpersonal, adaptability, stress management, and general mood) ( Bar-On, 2004). Validity of instruments were not investigated for the purpose of this review, however Crowne et al (2017) stipulate their own evidence-based rationale for use of MLQ and EQ-I (p.223). Before and after survey findings reported EI could be improved following education, the study further advocating that organisation's use a long-term EI programme to improve leadership of NLs and foster positive workplace culture.…”
Section: Personal Traitsmentioning
confidence: 99%